Electron beam sterilization - Abdullah, Nor Rul Hasma (2004)
The project consists of three stages. The fust stage demonstrates, through experimental works on the highvoltage deck of electron beam accelerator unit; filament control circuit board and beam control circuit boards. In these circuit boards, an analog signal flows from low voltage sides via optical link cable to the ground and transmitted to the highvoltage side. The calibrations were made to ensure its safe operation. The second stage was to generate a new method of filament control and beam control circuit by constructing a Programmable Logic Controller (PLC) using the STEP 7- MicroIWIN32 and SIMA TIC WinCC software provided by SIEMENS AG. It is capable to operate under a highvoltage potential. It uses a PROFIBUS technology as the central connecting link for digital signal flow in the system. The advantages of the digital solution are the speed of data transmitting in both directions are faster and better signal to noise ratio (SNR) than analog solution. Finally, as the circuits in both projects were operated under a highvoltage potential, there would be a conflict with the transient voltage upon the components, equipments and cables installed in the circuits. Therefore, in the third stage, one circuit protection was created and examined to show transient voltage fault investigation methods and possible solutions. At the end, the project is attempted to expand the automation technology in highvoltage area and support future development in this area